APLIKASI TPACK DALAM MATA KULIAH STATISTIK DASAR PADA MAHASISWA CALON GURU - Rohman; Rahma Siska Utari; Lis Amalia (FKIP Universitas Tamansiswa Palembang, 2022)
This study aims to describe the integration of technological pedagogical content knowledge (TPACK) when making teaching implementation plans and during the implementation of learning in basic statistics courses at the Faculty of Teacher Training and Education, Sjakhyakirti University. This study uses a qualitative descriptive method with the object being studied is the Learning Implementation Plan and the learning process carried out by the subject lecturers and researchers, student teacher candidates who teach basic statistics courses in the first semester are the subjects in this study, while data collection techniques by using interviews, observation and documentation. The results of this study indicate that the integration of technological pedagogical content knowledge (TPACK) is grouped into three parts which include the integration of technological knowledge (TK), namely the teaching plan that has optimized technology, the integration of pedagogical knowledge (PK), which includes the planning of teaching methods, and the integration of content knowledge ( CK) that is, the material is in accordance with the expected competence. The learning process produces four activities to support statistical literacy skills, namely data awareness (the importance of data in life and how to collect it), Statistics conceptual and Idea (managing good and correct data), representative data (presenting and visualizing data), and data interpretation (interpreting data to draw a conclusion)